Analisis Efektivitas Pengelolaan Anggaran Di Kabupaten Kepulauan Siau Tagulandang Biaro - Tamasoleng, Adelstin (JURNAL RISET BISNIS DAN MANAJEMEN)
The result of this research indicates that although the leader and staff in regency understand the meaning of using performance based budgeting, but start from planning that is formula ofstrategic plan, the planning of program and activity ,Â  implementation, the report and accountability until the work evaluation, is not fully conducted yet according to the law andtheory of performance based budgeting. The face hindrance are : human resources factor, the lack of information and data (financial as well as non financial), the scale of prioritywhich are not formulated clearly, the measurement of unsame performance, the unclear work indicator, the limit of fund and the lack of commitment, there is still political influence,accounting system and information system based on technology (IT).Keywords : Descriptive, performance based budgeting, hindrance